Stabilization of horn fracture using cross pinning with ozonated autohaemotherapy in a Kangayam bull - Kshirsagar, Saurav; Tina Roshini, S.; Gurunathan, N.; Vigneshwari, M.; Naga Sai Sravya, Ramisetty; Vasanthanathan, D.; Priyatharshini, B. Dayana; Arul Jothi, N. (Indian Journal of Veterinary Surgery, 2025)
.